2006
DOI: 10.1098/rspb.2006.3688
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection predicts advancement of avian spring migration in response to climate change

Abstract: Global warming has led to earlier spring arrival of migratory birds, but the extent of this advancement varies greatly among species, and it remains uncertain to what degree these changes are phenotypically plastic responses or microevolutionary adaptations to changing environmental conditions. We suggest that sexual selection could help to understand this variation, since early spring arrival of males is favoured by female choice. Climate change could weaken the strength of natural selection opposing sexual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 63 publications
1
73
3
Order By: Relevance
“…tail length, which showed a trend towards larger values (Møller 2004, Møller & Szép 2005. However, at the interspecific level, Spottiswoode et al (2006) found that the relationship between the advancement of spring migration and the strength of sexual selection was stronger for changes in the median migration date of whole populations than for changes in the timing of first-arriving (male) individuals, suggesting that selection has not only acted on protandrous males.…”
Section: Introductionmentioning
confidence: 78%
“…tail length, which showed a trend towards larger values (Møller 2004, Møller & Szép 2005. However, at the interspecific level, Spottiswoode et al (2006) found that the relationship between the advancement of spring migration and the strength of sexual selection was stronger for changes in the median migration date of whole populations than for changes in the timing of first-arriving (male) individuals, suggesting that selection has not only acted on protandrous males.…”
Section: Introductionmentioning
confidence: 78%
“…This fact prevented us from quantifying change in migration phenology in relation to local climate, because climate during any part of the migratory path could potentially affect change in phenology (44,45). Therefore, we analyzed change in phenology over time, assuming that such change was due to change in climate, as has been done in other studies (8,9,21,35,46,47). Changes in migration dates were the slope of the simple linear regression of migration date on year, expressed as days/year.…”
Section: Methodsmentioning
confidence: 99%
“…We predicted that migratory bird species that did not anticipate timing of spring migration (i.e., that did not show a phenological response to climate change) should demonstrate declining populations, while taking into account several variables previously shown to be associated with population trends (see above and 12-19) or response to climate change. Among variables potentially affecting the phenological response to climate change, we considered migration distance, intensity of sexual selection, and total population size; a small population size, and thus lack of genetic variation, potentially could explain lack of response to climate change (8,9,21,22). All analyses were performed while accounting for phylogenetic relatedness among species by using phylogenetically independent linear contrasts (23).…”
mentioning
confidence: 99%
“…Sheriff 2012, unpublished observations). Similarly, males of many migratory bird species have advanced spring arrival more substantially than females [99], and in geese, adults may moult at progressively different times than their young [100]. Clearly, we need to understand mismatches on the level of individuals and populations to fully appreciate effects of global warming and climate-induced disruptions between interacting trophic levels.…”
Section: (A) Climate Changementioning
confidence: 99%